Rethinking Success: Music in Higher Education - Bennett, Dawn (Common Ground Publishing Pty Ltd, 2012)
Success, for the majority of performing arts majors, is defined as a performance career; and yet very few graduates achieve this goal. This paper draws on earlier research into the working lives and economic circumstances of instrumental musicians to consider how the goals of higher education music might be redefined for this cohort, and how this redefinition might be approached with students. Given the multiplicity of roles in which most musicians engage in order to sustain their careers, the research questions the concept of a musician as a performer, positing that a musician is rather someone who practices within the profession of music within one or more specialist fields. Whilst the paper considers instrumental music as its subject, the strategies for engaging students in future-focused conversations have broad relevance.